10 Things Software Developers Should Learn about Learning. - BROWN, NEIL C. C.; HERMANS, FELIENNE F. J.; MARGULIEUX, LAUREN E. (Communications of the ACM, 2024)
The article discusses what research has shown about human learning and memory, in the context of the need of software developers to engage in continuous learning throughout their careers. Topics include working memory vs. long-term memory, how human memory differs from computer memory, how problem-solving works, and whether there is any way to predict computer programming ability.